The Effectiveness of Yogurt and Papaya Juice Consumption on Constipation Incidence in Third Trimester Pregnant Women - Veni Suhendra; Arlina Rachmaida; Lydia Febri Kuniatin (Borneo Scientific Publishing, 2025)
Constipation in pregnant women in their third trimester is a significant health problem with a prevalence of 9.67% at the Rasau Jaya Community Health Center. If not properly treated, constipation can trigger serious complications such as hemorrhoids and bleeding, so an effective solution is needed to improve the quality of life of pregnant women. This study aims to determine the effectiveness of yogurt and papaya juice consumption in treating constipation in pregnant women in their third trimester at the Rasau Jaya Community Health Center, Kubu Raya District. This study used a quantitative method with a quasi-experimental design and a two-group pre-post test approach. The results showed different effectiveness between the two interventions. In the yogurt group, the mean constipation score decreased from 21.65 before the intervention to 10.40 after the intervention, indicating that constipation was resolved (indicator value <15). Statistical test results showed a p-value of 0.000, proving the effectiveness of probiotic yogurt in treating constipation. Meanwhile, in the papaya juice group, the mean score decreased from 22.10 before the intervention to 18.50 after the intervention. Although there was a decrease in the mean score, constipation in this group was not completely resolved, even though the p-value of 0.000 also indicated the effectiveness of papaya juice. In conclusion, yogurt proved to be more effective than papaya juice in treating constipation in pregnant women in their third trimester at the Rasau Jaya Community Health Center, Kubu Raya District.